Prevalencia de Ancylostoma spp y Uncinaria spp en caninos en el barrio de Lasso del cantón Latacunga. - Ballin Chancusig, Jennifer Marisol (2022)
The research relates to the infestation of different nematodes or endoparasites representing a risk for people, especially in children and older adults, which can cause gastrointestinal, visceral and neurological alterations. The objective of the research was to characterize the prevalence of Ancylostoma sp and Uncinaria sp in canines in the Lasso neighborhood, Latacunga. The method used was the flotation technique known as Sheather's Sucrose method, where the population was 100 canines. The result found in the Lasso neighborhood in the canton of Latacunga had parasite eggs with the highest prevalence of Coccidias in 17%, Toxocara canis in 14%, Trichuris in 13%, Taenia in 10%, Ancylostoma sp in 5% and Uncinaria sp in 2%. Regarding the prevalence associated with sex and age, the Chi-square test was applied and the results showed that the p-value for sex associated with Ancylostoma sp was <0.05, in other words, males have a greater presence of Ancylostoma sp eggs than females; and the results associated with sex associated with Uncinaria sp the p-value was >0.05; that is, both females and males have the same presence of Uncinaria sp eggs. The results of the prevalence associated with age for both Ancylostoma sp and Uncinaria sp, the p-value was >0.05 in both parasites, therefore, the presence of eggs of both parasites is present at any age. The nematodes or parasites of study have a very low prevalence, in due course it is necessary to emphasize the parasites with the highest prevalence.